THE PUBLIC OPPOSES (Islamic Sciences Journal, 2023)
Praise be to God, Lord of the worlds, and peace and blessings be upon our master Muhammad and his whole family and companions, and after: For the science of fundamentals is a broad field science, it is only entered by anyone who was in all the sciences, and the principles of jurisprudence existed with the presence of jurisprudence, but it was not recorded, but his issues were in the books of jurisprudence or on the tongues of jurists, and the first without him and collecting his issues was Imam Al-Shafi’i, may God have mercy on him Almighty in his book Al-Risala, after which several books were written, and this science had its own terms, expressions that limit it, and concepts that explain it, among these terms is: (public opposes), which is the name of my research that I want to show, and reveal its truth, by analyzing the concept and mentioning examples , And I had no difficulty collecting it except for lack of time and for accuracy and honesty.
Keywords: General - Fundamentals - Jurisprudence - Absolute - Conflict .